A Research on Warehouse Operation Optimization of Logistics Center. Issue 2 (January 2021) - Feng, Xiwen; Zhou, Yu; Gao, Mengying
Abstract: This article through to A logistics center warehouse on the production line are analyzed in the value stream, together with the present situation of the company, mapping of the value stream status quo of the existing production lines, using the picture, find out the current value of the production mode in operation, then put forward to reduce or eliminate non-value added link, map out the improved value stream map, and several Suggestions for improvement are put forward.